Ausweis von Vorranggebieten für Industrieansiedlungen in Thüringen - Bergfeld, Annedore; Groß, Ina-Beate (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
In 1998 a study was conducted on behalf of the Free State of Thuringia with the aim of determining priority areas to provide sites for major commercial and industrial enterprises planning to locate in the state. Unlike the so-called “commercial space potential model” in use in the Saarland, which in order to safeguard the supply of land for business premises constantly scans all sites becoming available with regard to their suitability for commercial use, the key feature of this study, which is based on a number of clearly defined areas, lay in the account it took of specific requirements placed on sites, and specifically of the abundance of sites available at the time of the study (over-supply of already serviced or designated commercial sites and of previously used commercial sites).